(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Among the factors that establish the pre‐analytical variability, some studies report that hemolysis is the main interferential in several tests. However, no studies were found on immunofluorescence tests or that using cell cultures. The aim of this study was to evaluate the interference of different degrees of hemolysis serum samples in the evaluation of virus neutralizing antibodies (VNA) by rapid fluorescent focus inhibition test (RFFIT). We obtained 27 blood samples from dogs vaccinated for rabies. Hemolysis was caused by mechanical induction and freezing. Hemolysated sera were classified visually and by measurement of hemoglobin made by spectrophotometry. The evaluation of VNA in the samples was performed by RFFIT. The results were statistically analyzed by the Mann‐Whitney test. Four samples and their hemolyzed aliquots were selected, added to BHK‐21 cell and maintained at 37°C for 20 hours to evaluate the interference caused by hemolysis. Sera were classified as without hemolysis (up 0.5), 1 + (0.6 to 1.0), 2 + (1.1 to 1.5), 3 + (1.6 to 2.6), 4 + (2.7 g / dL or more). The results of VNA titers showed differences when we compared the serum without hemolysis with 2 +, 3 + and 4 + however, this difference was not statistically significant (P>0.05). The reading of the results was difficult in the first dilution of sera with 2 + hemolysis by irregular cell growth, and in sera with 3 + and 4 + for the formation of clusters and cell death. It is concluded that hemolysis can interfere with antigen‐antibody or virus‐cell binding and has a high degree of interference in sera with 3 + and 4 + by lysing the cell or changing its growth pattern.